Press, politics and race in Guyana - Mohamed, Paloma (2003)
Focuses on the print media. Concludes that the press in Guyana evolved as mouthpieces for special interests. Notes that the press consistently made a significant contribution to economic and socio-political conditions existing in Guyana.